Environmental Education in the school context: An analysis of the National Common Curricular Base (BNCC) and the Curricular Document Referential Da Bahia (DCRB) - Lobo, Darline; Rocha, Emerson Antônio (Seven Editora, 2023)
Currently, society has been debating and guiding environmental problems with higher frequency due to the worsening in the past few years, illustrating the need to incentivize even more the environmental practices at the school level. Literature shows that besides the EE (Environmental Education) isn’t well implemented in Brazilian schools, plenty of institutions have adapted their spaces to the EE guided by documents from few government institutions. In Brazil, there are plenty of official Documents about the improvement of education an example, CNCB and BRCD represent excellent support and orientation tools to managers and educators, which must follow and get based on their rules, objectives, and established standards. So, the contents must be contextualized with other curricular components, becoming a tool for knowledge of health and environment, promoting than the EE. The present article has the main objective of analyzing the approach of the CMCB and BRCD. The methodology used for the construction of this article where qualitative research using a Documental Analysis (DA) inspired at a Bibliographic Review (BR). For the construction of this article were made a characterization and conceptualization of the EE. Then, were presented two base documents for this work, the CMCB, and BRCD, where were pointed the main directions about EE and each one of them approach it. After this, were observed in each document, this teme approach has different levels and developments, which has shown a discrepancy in the valorization between CMCB and BRCD. So, exists a clear need to discuss continuously and permanently EE in CMCB due to the relevance that this document has at the National level for guarantee an effective EE, multidisciplinary and critical-reflective. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-016